2020
DOI: 10.3389/fcvm.2019.00190
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Myocardial Motion and Deformation Analysis

Abstract: Information about myocardial motion and deformation is key to differentiate normal and abnormal conditions. With the advent of approaches relying on data rather than preconceived models, machine learning could either improve the robustness of motion quantification or reveal patterns of motion and deformation (rather than single parameters) that differentiate pathologies. We review machine learning strategies for extracting motion-related descriptors and analyzing such features among populations, keeping in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 93 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…e usage of deep learning methods shown in Figure 1 supports reducing the computation time and enables normalising the data for better accuracy. Many researchers have noted that the usage of deep learning models supports greatly in analysing the data very effectively and the dataset can be increased through the usage of deep learning models these aspects can be effectively analysed [4]. Deep learning tools like multilayer neural networks enable performing the classification of data sets in heart-related diseases with more accuracy when compared with the traditional models.…”
Section: Introductionmentioning
confidence: 99%
“…e usage of deep learning methods shown in Figure 1 supports reducing the computation time and enables normalising the data for better accuracy. Many researchers have noted that the usage of deep learning models supports greatly in analysing the data very effectively and the dataset can be increased through the usage of deep learning models these aspects can be effectively analysed [4]. Deep learning tools like multilayer neural networks enable performing the classification of data sets in heart-related diseases with more accuracy when compared with the traditional models.…”
Section: Introductionmentioning
confidence: 99%
“…The low-dimensional embedding of myocardial shape or motion/deformation has been thoroughly explored in research, as reviewed in (Gilbert et al, 2020;Duchateau et al, 2020). Nonetheless, shape and deformation should not be considered independently from each other.…”
Section: Analyzing Myocardial Shape and Deformationmentioning
confidence: 99%
“…The networks mentioned above have been applied to cardiac imaging, with a main focus on MRI [13]- [16]. In parallel, a pilot study has recently shown the adaptability of FlowNet-based networks to the characteristics of ultrasound images for motion estimation [2].…”
Section: Introductionmentioning
confidence: 99%